Given Abel's Identity according to Apostol [1] it follows that,

$\sum_{y <n\leq y} a(n) f(n) = A(x) f(x) - A(y) f(y) - \int\limits_y^{x} A(t) f'(t) dt\quad\quad\quad$

where $A(x) = \sum_{n\leq y} a(n)$

I am having trouble understanding some steps in the proof namely line 4, 5 & 6 below that concerns the Riemann sum to integral that he performs; I cannot understand how he transforms the sum to integral shown in $\color{blue} {blue}$ in the following proof:

PROOF. Let $k=[x]$ and Let $m=[y]$ so that $A(x)=A(k)$ and $A(y)=A(m).$


$$\sum_{y <n\leq x} a(n) f(n) = \sum_{n=m+1}^{k} a(n) f(n) = \sum_{n=m+1}^{k} [A(n)-A(n-1)] f(n)$$

$$= \sum_{n=m+1}^{k} A(n) f(n)-\sum_{n=m}^{k-1} A(n) f(n+1)$$

$$= \sum_{n=m+1}^{k-1} A(n) [f(n)-f(n+1)] + A(k) f(k) - A(m) f(m+1)$$

$$= -\sum_{n=m+1}^{k-1} A(n) \color{blue}{\int_n^{n+1} f(t)'dt} + A(k) f(k) - A(m) f(m+1)$$

$$= -\sum_{n=m+1}^{k-1} \color{blue}{\int_n^{n+1} A(t)f(t)'dt} + A(k) f(k) - A(m) f(m+1)$$

$$= - \color{blue}{\int_{m+1}^{k} A(t)f(t)'dt} + A(x) f(x) - \color{blue}{\int_{k}^{x} A(t)f(t)'dt} - A(y)f(y) - \color{blue}{\int_{y}^{m+1} A(t)f(t)'dt}$$

$$= A(x) f(x) - A(y) f(y) - \int\limits_y^{x} A(t) f'(t) dt$$

[1] Apostol page 77 "Tom M. Apostol-Introduction to Analytic Number Theory-Springer (1976)


There is a minor mistake in your definition of $A(x)$, it should be

$$A(x) = \sum_{n \le \color{red}x} a(n)$$

From the third line to the fourth line, it is due to

$$\int_n^{n+1}f(t)' \,dt = f(n+1)-f(n) $$

From the fourth line to the fifth line, it is due to

$$\forall t \in [n, n+1), A(t) = A(n) $$


$$\int_n^{n+1} A(t) f(t)' \, dt= \int_n^{n+1} A(n) f(t)' \, dt = A(n)\int_n^{n+1} f(t)' \, dt.$$

From the fifth line to the sixth line, the first term is just

$$\sum_{n=m+1}^{k-1} \int_n^{n+1} A(t)f(t)' \, dt = \int_{m+1}^k A(t) f(t)' \, dt$$

We are just splitting the integral up.

The second and third term is due to

$$\forall t \in [k,x], A(t)=A(k)=A(x),$$


$$\int_k^x A(t) f(t)' \, dt = A(k) \int_k^x f(t)' dt = A(k) [f(x)-f(k)]=A(k)f(x)-A(k)f(k)=A(x)f(x)-A(k)f(k).$$

For the fourth and fifth term, it is due to

$$\forall t \in [y, m+1), A(t) = A(y)=A(m),$$


$$\int_y^{m+1} A(t)f(t)' \, dt = A(y) \int_y^{m+1 } f(t)' \, dt = A(y) [f(m+1)-f(y)]=A(m)f(m+1)-A(y)f(y)$$

  • $\begingroup$ thanks for the detailed explaination but I wonder why $A(k)f(x)-A(k)f(k)=A(x)f(x)-A(k)f(k)$? Also isn't there a A(x) missing outside the LHS of $\sum_{n=m+1}^{k-1} \int_n^{n+1} f(t)' \, dt = \int_{m+1}^k A(t) f(t)' \, dt$? $\endgroup$ – onepound Oct 4 '18 at 8:11
  • $\begingroup$ Hi, thanks for pointing the error. we have $A(k)=A(x)$ since $k = \lfloor x \rfloor$ $\endgroup$ – Siong Thye Goh Oct 4 '18 at 8:36
  • $\begingroup$ okay but would that not make $A(k)f(x)−A(k)f(k)$ equal zero if $A(k)=A(x) $? $\endgroup$ – onepound Oct 4 '18 at 17:05
  • $\begingroup$ $f(x)$ need not be equal to $f(k)$. so it need not be zero. $\endgroup$ – Siong Thye Goh Oct 4 '18 at 17:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.